Fe–Nx active sites embedded into metal–organic-framework-derived mesoporous carbon for highly efficient oxygen reduction. (May 2023) - Li, Tianjiao; Li, Yan; Wang, Han; Yu, Jie; Xu, Dan; Wang, Heng-guo
Abstract: Fe-Nx /C materials have proven to be one of the most promising electrocatalysts. However, it is impractical to increase the loading of Fe-Nx only by increasing the Fe content in the catalyst. Too much Fe content will lead to its aggregation into Fe nanoparticles during the pyrolysis process. In contrast to Fe-Nx, the formed Fe-nanoparticles result in many metal atoms inside the catalyst that cannot directly act as active sites, thus losing some of the electrocatalytic activity. Herein, we synthesized Fe-Nx /mesoporous carbon materials (FeTA -Nx /NC-900) by stepwise pyrolysis using MIL-101 with larger porosity as the structural substrate and iron tetraaminophthalocyanine (FeTAPc) as the Fe dopant source. The composite has high porosity with rod structure that can effectively stabilize Fe-Nx sites, large specific surface area, and higher atom utilization for high dispersed Fe-Nx active sites. Especially, FeTA -Nx /NC-900 exhibits ORR half-wave potentials of 0.82 V and 0.65 V in alkaline/acidic media, respectively. Moreover, FeTA -Nx /NC-900 exhibits a peak power density of 74.3 mW cm −2 and excellent stability of more than 55 h when it is used as the cathodic electrocatalyst in Zn-air battery. Graphical abstract: Fe–Nx active sites were embedded in metal-organic-framework-derived mesoporous carbon using the two-step pyrolysis strategy, and the optimum samples exhibit good electrochemical performance as an electrocatalyst for oxygen reduction reaction and zinc-air batteries. Image 1 Highlights: A two-step pyrolysis strategy is proposed to prepare high-performance electrocatalysts. Fe-Nx active sites are embedded in metal-organic-framework-derived mesoporous carbon. The samples exhibit good electrochemical performance for oxygen reduction reaction. The resulting electrocatalyst exhibits high-performance for zinc-air batteries.